Anti-obesity potential of polygonum minus huds.: in vitro and in vivo evaluation - Arshad, Zulika; Sofian-Seng, Noor-Soffalina; Afzan, Adlin; Mohmad Misnan, Norazlan; Alias, Norsyuhada; Kamal, Norkhalida; Mediani, Ahmed; Abdul Rahman, Hafeedza (John Wiley and Sons Inc, 2024)
Polygonum minus (PM) has a rich traditional usage for health benefits, yet its potential as a natural-based solution for obesity management remains unexplored. This study evaluated the antioxidant properties, inhibition of pancreatic lipase and α-glucosidase activities, and metabolite profiles of PM aerial extracts harvested at 8, 10, and 12 weeks using 1H NMR-based metabolomics. PM harvested at 12 weeks exhibited significant antioxidant and enzyme inhibition activities. NMR metabolomics unveiled nine major metabolites correlated to the bioactivities of 12-week PM. LC–MS/MS profiling enabled the identification of flavonoids and phenolic acids, with the majority having sulfate, gallate, and glycoside moieties. Notably, in vivo experiments demonstrated that rats treated with 200 mg kg−1 and 400 mg kg−1 PM exhibited significantly lower (P < 0.05) total body weight gain (39.03% and 52.59%, respectively) compared to negative control rats (69.95%), with the lower dose group also exhibiting reduced (P < 0.05) fasting blood glucose levels. This study highlights the potential of 12-week PM as a natural-based solution in obesity management.